Advanced visualization and simulation techniques for modern construction management. Issue 5 (August 2014) - Rohani, Mohammad; Fan, Mizi; Yu, Chuck
Visual simulation has emerged as a key planning tool for an intended built environment because it enables architects, engineers and project managers to visualize the evolution of a construction process before a project starts. The process thus enables efficient construction, reducing time and cost through planning and controlling resources, machines and materials. On the other hand, construction industry has evolved from traditional on-site building to offsite modern methods of construction (MMC). Highly efficient and effective onsite planning and management processes are urgently needed, and this would require implementing visual techniques in MMC to provide a powerful management platform for planning and controlling projects. Development in MMC is important as the technique can enable higher degree of air-tightness in buildings necessary for energy-efficient passive homes and would minimize waste generation, thus contributing to a sustainable development. This project reviews the simulated operational assembly-line process for on-site MMC using visualization techniques. 4D-CAD has been integrated for simulation of construction operation, superimposed to video taken by fix tablets (ipad2). Augmented reality (AR) scenes of project process can be introduced in planning stage to implement decision making for various built environments required. This paper is the first of a series of papers from this study, which provides a review of researches that have been carried out in planning and controlling of construction operation using visualization techniques and to address some issues relating to existing visualization techniques for MMC.